Relationship between Genetic Variant of OXTR (rs53576) and MTNR1B (rs1387153) and Symptoms of Psychological Stress in Females with Gestational Diabetes Mellitus - Abid, Fatima; Ahmed, Sadaf; Noushad, Shamoon; Farhat, Sabah; Fatima, Syeda Sadia (Journal of the Pakistan Medical Association, 2023)
Objective: To assess the association of oxytocin receptor (rs53576) and melatonin hormone receptor 1B (rs1387153) gene single nucleotide polymorphisms with psychological symptoms in women with gestational diabetes mellitus. Method: The case-control study was conducted from May 1 to June 1, 2022, at the Department of Physiology, University of Karachi, in collaboration with the Department of Biological and Biomedical Sciences, Aga Khan University, Karachi, and the Department of Obstetrics and Gynaecology, Jinnah Postgraduate Medical Centre, Karachi. Fifty gestational diabetic pregnant women (group A), and ninety healthy pregnant women (control group B) were recruited. Sanger sequencing was performed to assess the genotypic frequency and polymorphic variation of all subjects. Perceived stress scale and diabetes-related distress scale were used to assess the stress levels. Data was analysed using SPSS 23. Results: Of the 140 subjects, 90 (64.3%) were controls with mean age 24.96±4.35 years, and 50 (35.7%) were cases with mean age 28.78±5.25 (p<0.05). Mean body weight and mean gestational age were not significantly different between the groups (p>0.05). Melatonin hormone receptor 1B rs1387153 frequency was significantly different between the groups (p<0.05). Among the cases, a significant mean difference for regimen distress scores between AA and GG was observed for oxytocin receptor rs53576 (p=0.04). A significant mean difference in sum of PSS, diabetes-related stress, total diabetes-related stress and emotional distress was noted between CC and TT genotypes for melatonin hormone receptor 1B rs1387153 (p=0.001). Conclusion: MTNR1B rs1387153 genotypes were associated with perceived stress, diabetes-related stress, diabetic distress, and emotional burden, while OXTR rs53576 genotypes were associated with regimen distress in GDM women. Key Words: Diabetes, Distress, Gestational diabetes mellitus, Genotypes, Stress, Psychological stress, Pregnancy.